2014
DOI: 10.3856/vol42-issue3-fulltext-6
|View full text |Cite
|
Sign up to set email alerts
|

Bases conceptuales para la aplicacion de una evaluacion de estrategias de manejo (EEM) en sardina comun (Strangomera bentincki) y anchoveta (Engraulis ringens) en la zona centro sur de Chile

Abstract: Bases conceptuales para la aplicación de una evaluación de estrategias de manejo (EEM) en sardina común (Strangomera bentincki) y anchoveta (Engraulis ringens)en la zona centro-sur de Chile RESUMEN. Se identifican los factores claves a considerar en el desarrollo de una evaluación de estrategias de manejo (EEM) para los recursos pequeños pelágicos en la zona de centro-sur de Chile, sardina común (Strangomera bentincki) y anchoveta (Engraulis ringens). En Chile, la EEM no ha sido aplicada al manejo de estas pes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Exogenous factors have been widely shown to have a direct and critical effect on the population dynamics of pelagic fish (Burbank et al, 2023; Lowerre‐Barbieri et al, 2017; Ospina‐Alvarez et al, 2022). For the anchovy from south‐central Chile, warm sea surface temperature (SST) conditions related to El Niño events were positively correlated with high recruitment (Cubillos & Arcos, 2002), while chlorophyll‐a was not significant in explaining recruitment (Arteaga et al, 2014; Gomez et al, 2012). Alternatively, Zunguza et al (2022) showed the relevance of river runoff as an important factor in explaining anchovy recruitment, suggesting that anomalies of freshwater input during the main reproductive period of anchovy affected both the survival of early life stages and recruitment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exogenous factors have been widely shown to have a direct and critical effect on the population dynamics of pelagic fish (Burbank et al, 2023; Lowerre‐Barbieri et al, 2017; Ospina‐Alvarez et al, 2022). For the anchovy from south‐central Chile, warm sea surface temperature (SST) conditions related to El Niño events were positively correlated with high recruitment (Cubillos & Arcos, 2002), while chlorophyll‐a was not significant in explaining recruitment (Arteaga et al, 2014; Gomez et al, 2012). Alternatively, Zunguza et al (2022) showed the relevance of river runoff as an important factor in explaining anchovy recruitment, suggesting that anomalies of freshwater input during the main reproductive period of anchovy affected both the survival of early life stages and recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this model was not selected as a predictive model to explain recruitment. Chlorophyll‐a has been established to explain the recruitment variability of pelagic fish in south‐central Chile (Arteaga et al, 2014; Gomez et al, 2012). In our study, the model that included chlorophyll‐a, wind, and spawning biomass showed a slight positive relationship and high deviance explained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation